ANALYSIS OF INTERNATIONAL STANDARDS FOR THE INVESTIGATION OF MONEY LAUNDERING CRIMES - Kudratillayev Xazratali Zokirjon o‘g‘li (Western European Studies, 2024)
The relevance and importance of the issues studied in the article are determined by the importance of eliminating legal contradictions that complicate the implementation of tasks by the competent law enforcement agencies of various states related to the detection of transnational and (or) international crimes, the identification of funds and other property obtained from such illegal activities, as well as their seizure and subsequent confiscation. The article provides information on the author's analysis of the formed international relations, the novelty and relevance of which are of scientific and practical importance for the further improvement of international law
Keywords: international cooperation; international treaties; conventions; directives